Extraction of Beta-Glucan from Sacchromyces boulardii, Study of its Chemical and Functional Properties, and Comparison of its Immunological Properties with Yeast Extracted from it - Abdel Reda, Zahraa; R. ALwaaili, Janan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The study was conducted to identify the immunomodulatory effect of beta-glucan and to compare its immunomodulatory properties with S.boulardii yeast. In this study, S.boulardii yeast was used to extract beta-glucan. The yeast was activated using a YPD medium, its purity was examined, and the following operations were performed on it: The biomass of S.boulardii yeast was grown in a vibrating incubator. The biomass was isolated, collected, washed, and dried. Extracting beta-glucan using the acid-base method for S.boulardii yeast is considered the best  extraction method. Beta-glucan was partially purified using 4% phosphoric acid. Chemical tests were conducted on it and its functional properties (ability to bind to fats and water) were evaluated. The biological experiment was conducted for thirty days by taking three groups,  each group containing five mice, A1 the control group, A2 the group fed with S.boulardii yeast, and A3 the group fed with beta-glucan extract. The effect of doses with treatments A1, A2, and A3 on the external appearance of the mice and the activity of the mice was studied. The effect of doses with treatments A2 and A3 was studied after the end of the starvation period on the final weight, and it was compared to treatment A1. It was noted that there were no significant differences at the level (P